Anatomical Approach to Clinical Problems of Popliteal Fossa - Dagur, Gautam; Gandhi, Jason; Smith, Noel; A. Khan, Sardar (Current Rheumatology Reviews, 2017)
Background: Popliteal fossa, also known as the popliteal space, is located behind the knee joint. This region can develop many clinical complications in the vascular, nervous, lymphatics, adipose, as well as swelling and masses. Objective: The objective of this review article is to give a detailed understanding of the popliteal fossa and the clinical pathology that may present itself. Methods: MEDLINE® searches were conducted of literature published since 1950s for “popliteal fossa,” “diseases,” “anatomy,” “arterial,” “venous,” “nerves,” “entrapment syndrome,” “aneurysms,” “cysts,” “lymphatics,” “solid masses,” “tumors,” “inflammatory lesions,” and “swellings.” The references provide up-to-date literature for all the pathologies discussed. Results: This review articles discusses the anatomy, clinical examination, including history, physical, and imaging modalities, and various diseases that present themselves in patients. Diseases relating to the arterial and venous systems, nervous system, musculature, adipose, lymphatics, cysts and other solid masses, including neoplasms, and abscesses. The differential diagnosis and symptoms of certain conditions are addressed to isolate the root of the manifestation. Conclusion: Diseases of the popliteal fossa can use histology and electrophysiology to aid in diagnosis, as well as instrumentation. Surgical approaches are uses to treat varying pathologies as they are the best means of therapy.
Keywords: persistent sciatic artery